Synthesis of Secondary Metabolites from Higher Fungi - Reck, Bernhard; Spiteller, Peter (Synthesis, 2015)
Higher fungi are a promising source of new bioactive natural products with great structural diversity, ranging from polyketides to terpenoids and alkaloids. Many of these structures are a challenge for synthetic organic chemists who have been inspired to develop new total syntheses. Nevertheless, reviews covering syntheses of fungal natural products are lacking. One aim of this review is to close this gap and to present a selection of more recent syntheses of fungal secondary metabolites from different structural classes. Secondly, this review intends to demonstrate that there are many more motivations for the synthesis of natural products than to confirm a proposed structure or to report the first total synthesis of a new natural product. Thirdly, this review is intended to stimulate the interest of organic chemists in the synthesis of fungal natural products.1 History and Importance of (Fungal) Secondary Metabolites2 Reasons for the Synthesis of Fungal Natural Products3 Total Syntheses of Selected Fungal Natural Products3.1 Terpenes3.1.1 Sesquiterpenes3.1.1.1 Polyquinanes3.1.1.2 Drimanes3.1.2 Diterpenes: Cyathanes3.1.3 Terpenes Containing a Butenolide Moiety3.2 Alkaloids3.3 Natural Products Derived from the Shikimate Pathway3.3.1 Pulvinic Acid Derivatives and Terphenyl Quinones3.3.2 Shikimate Pathway Derived Macrolides3.3.3 Strobilurins3.4 Aromatic Polyketides3.4.1 Quinones3.4.2 Resorcylates and Catechols3.5 Sugar Derivatives4 Conclusion and Outlook
Keywords: biological activity; biomimetic synthesis; fungi; natural products; total synthesis